Comparative Efficiency of Different Surfaces for Drying Fish - BASU, SUBRATA; KHASIM, D. IMAM; RAO, P. SRINIVASA (Fishery Technology, 2017)
The efficiency -0f four different drying suifaces, namely, cement p1atfor.m, pa1myrah leaf mat, aluminium tray and stretched net for drying fish were studied using sciaenids, mullet and perch. All the drying surfaces wete found to be equally efficient. The cheaper and locally available palmyrah leaf mat or stretched net can replace costly cement platform and aluminium tray for efficient drying of :fish.